1995
DOI: 10.1111/j.1476-5381.1995.tb15952.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sympathetic vasoconstriction in pigs in vivo by the neuropeptide Y‐Y1 receptor antagonist BIBP 3226

Abstract: 4 High frequency stimulation of the sympathetic trunk in control pigs caused a biphasic vasoconstrictor response in nasal mucosa, hind limb and skin: there was an immediate, peak response, followed by a long-lasting vasoconstriction. BIBP 3226 (1 and 3 mg kg-1) reduced the second phase by about 50% but had no effect on the-peak response. In the spleen, kidney and mesenteric circulation (which lack the protracted response) BIBP 3226 was likewise without effect on the maximal vasoconstriction, and did not influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 46 publications
(53 reference statements)
10
66
1
Order By: Relevance
“…The NS, as well as NE and ATP, induced vasoconstriction was potentiated by a NPY-Y 1 agonist and attenuated by BIBP3226 [76]. Similar results have been seen in vivo, where BIBP3226 inhibited the vasoconstrictor response to high frequency stimulation of sympathetic nerves in nasal mucosa, hindlimb and skin [74]. These results clearly suggest that endogenous NPY, acting on a Y 1 receptor, plays a role in producing long-lasting vasoconstriction in these organs or tissues.…”
Section: Functional Npy Responsivenesssupporting
confidence: 83%
See 1 more Smart Citation
“…The NS, as well as NE and ATP, induced vasoconstriction was potentiated by a NPY-Y 1 agonist and attenuated by BIBP3226 [76]. Similar results have been seen in vivo, where BIBP3226 inhibited the vasoconstrictor response to high frequency stimulation of sympathetic nerves in nasal mucosa, hindlimb and skin [74]. These results clearly suggest that endogenous NPY, acting on a Y 1 receptor, plays a role in producing long-lasting vasoconstriction in these organs or tissues.…”
Section: Functional Npy Responsivenesssupporting
confidence: 83%
“…For instance, the long-lasting vasoconstriction induced by high frequency stimulation of sympathetic nerves of the guinea pig vena cava in vitro was significantly attenuated in the presence of SR 120107 [73] or BIBP3226 (both selective NPY-Y 1 antagonists) [74,75]. It was also observed that sympathetic nerve stimulation (NS) produced concomitant vasoconstriction and NPY-ir release in the isolated perfused mesenteric arterial bed.…”
Section: Functional Npy Responsivenessmentioning
confidence: 91%
“…In food-restricted rats (with high endogenous NPY tone), the central effects of NPY Y 2 receptor stimulation dominated, which resulted in an increase of MAP and HR. Conversely, the peripheral effects of NPY Y 2 receptor stimulation dominated in HFD-fed rats (with low central NPY tone), which tended to decrease HR probably due to presynaptic inhibition of sympathetic neurotransmitters such as norepinephrine (16,18,23). The fact that blood pressure did not decrease after PYY in HFD-fed rats, which probably had an increased sympathetic tone, could be due to regionally selective vascular effects of Y 2 receptor stimulation.…”
Section: Discussionmentioning
confidence: 94%
“…For example, using electrical field stimulation in excised vascular segments, the vasoconstrictor response includes an immediate peak response followed by a long-lasting vasoconstriction. This second component is not eliminated by reserpine indicating that it includes a nonadrenergic stimulus (173) which is reversed by BIBP 3226 ((2R)-5-…”
Section: Sympathetic Neurotransmitters Cotransmitters and Receptorsmentioning
confidence: 96%